Inovasi dan Tantangan Penggunaan Artificial Inteligence dalam Hukum Maritim di Era Transformasi Digital - Nurul wahdatulnisa; Imam Fadhil Nugraha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Artificial intelligence (AI) is now an integral part of the digital transformation of various industries including the maritime sector. In the context of maritime law, AI has the potential to optimize various aspects ranging from maritime traffic management, Accident risk mitigation to monitoring international environmental maintenance. However, the application of AI also presents a variety of very complex challenges. This research highlights the legal, regulatory and ethical challenges that arise along with the application of AI in the maritime sector. Among them are the lack of clarity regarding legal responsibility for incidents involving autonomous ships, the lack of international standards governing the use of AI in operations maritime, as well as threats to data privacy and security from the use of increasingly sophisticated technology. Apart from these challenges, This research also discusses innovations that are already developing, such as the development of new legal frameworks for maritime AI, blockchain integration technology in the supply cycle chain as well as cross-border collaboration to developing regulatory standards that are cohesive and responsive to technological developments, this research concludes that to ensure the safe and responsible implementation of AI in the maritime sector, a multidisciplinary approach involving law, technology and international cooperation is needed, AI can be the main catalyst in creating a safer, more efficient and sustainable maritime ecosystem in the future.